Determinants of Financial Structure and their Impact on Banking Performance - Dr. Ahmed Risian Albahadly; Husam A. Ali Al-Hashemi (Research Parks Publishers, 2023)
Purpose: The study aims to understand Iraqi commercial banks' behavior toward their financial structures and evaluate their performance using the standard equation method and the Panel Data method. Theoretical framework: An increase in financial leverage leads to an increase in the required rate of return on equity due to the high risk faced by shareholders, is concluded in a theory of corporate finance. There are internal and external determinants that affect the financial structure of a bank and their performance as well. External determinants include taxation policy, inflation rates, and the situation of financial markets while internal determinants include bank size, asset structure and growth rate. However, Iraqi banking sector witnessed major changes due to the openness and reconsidering the existing regulations and laws and dealing with the data of globalization era. Design/methodology/approach: The approach of this research is to find the banking performance of Iraqi banks by incorporating the size of bank, the structure of bank’s assets and growth of banks as determinants and return on assets (ROA) is taken as an indicator of banking performance. Multiple regression was applied using the Panel Data method to test the ability of the independent variables in explaining and understanding the dependent variable.The study, which was applied on 13 Iraqi commercial banks registered in the Iraq Stock Exchange during the period 2007-2021. Findings: The results of the study shows that the size of the bank, the structure of the bank’s assets, and the bank’s growth are the determinants that have a significant impact on the banking performance represented by the return on assets (ROA). The major impact on the banking performance is the structure of the assets of the Iraqi banks because they keep their money within these assets, which affects the banking performance. The standard equation proved that the other effect is the growth rate of the banks. Finally, the size of the bank is shown to have the least impact on the evaluation of banking performance. Research, Practical & Social implications: The contribution of this research study demonstrated that using ROA (return on assets) could become helpful in analyzing effectively significant impact of size, structure and growth of banks. Balanced financial structure works more accurately by providing proper support to the managerial level. Originality/value: To date, and to the best of the knowledge of researchers, most of the previous research studies have focused the impact of capital structure towards performances of banking sector in Iraq, but this study investigates the determinants of financial structure and their impact on banks’ performance in Iraq.